Kevin Arnsberg: capstone - Arnsberg, Kevin, artist (Colorado State University. Libraries, 2015)
The artist's statement: I have always been attracted to the ominous qualities of the night. As I make my way through the dark, I seek colors and atmospheric conditions that call attention to places that often go overlooked. The images contain a radiance in the colors that I am able to capture when using a medium format film camera and chromogenic color prints. These photographs are my pursuit to call attention to the intriguing nature of color at night.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.